Impact of Citrus Pulp or Inulin on Intestinal Microbiota and Metabolites, Barrier, and Immune Function of Weaned Piglets - Uerlings, Julie; Arévalo Sureda, Ester; Schroyen, Martine; Kroeske, Kikianne; Tanghe, Sofie; De Vos, Maartje; Bruggeman, Geert; Wavreille, José; Bindelle, Jérôme; Purcaro, Giorgia; Everaert, Nadia (Frontiers in Nutrition, 2021)
We investigated the use of citrus pulp (CP) as a novel prebiotic capable of exerting microbiota- and immuno-modulating capacities to alleviate weaning stress. Inulin (IN), a well-known prebiotic was used for comparison. Hundred twenty-eight male weaned piglets of 21 days old were assigned to 32 pens of four piglets each. Piglets were assigned to one of the four treatments, i.e. control, inulin supplemented at 0.2% and CP supplemented either at 0.2% (CP0.2%) or at 2% (CP2%). On d10-11 and d31-32 postweaning, one pig per pen was euthanized for intestinal sampling in order to evaluate the growth performance, chyme characteristics, small intestinal morphology, colonic inflammatory response and barrier integrity, metabolite profiles (GC-MS and LC-MS) and microbial populations. The IN and the two CP treatments induced higher small intestinal villus height to crypt depth ratios in comparison with the control diet at both sampling times. All treatments decreased acidic goblet cell absolute counts in the crypts in comparison to the control diet of the duodenum on d10-11 and d31-32. Gene expression of β-defensin 2 (DEFβ4a) was down-regulated in colonic tissues following IN and CP2% inclusion on d31-32. On d31-32, piglets fed with IN and CP0.2% showed lower mRNA levels of occludin and claudin-3, respectively. Not surprisingly, flavonoids were observed in the colon in the CP treatments. Increased colonic acetate proportions on d10-11, at the expense of branched-chain fatty acid levels, were observed following CP2% supplementation compared to the control diet, inferring a reduction of proteolytic fermentation in the hindgut. The beneficial microbial community Faecalibacterium spp was promoted in the colon of piglets fed with CP2% on d10-11 (P = 0.04; FDR non-significant) and on d31-32 (P = 0.03: FDR non-significant) in comparison with the control diet. Additionally, on d31-32, CP2% increased the relative abundance of Megasphaera spp compared to control values (P = 0.03; FDR non-significant). In conclusion, CP2% promoted the growth of beneficial bacterial communities in both post-weaning timepoints, modulating colonic fermentation patterns in the colon. The effects of CP supplementation were similar to those of IN, and showed potential as a beneficial feed supplement to alleviate weaning stress.